Indonesian 'Saracen' Syndicate and the Legal Gap for Hoax Eradication in Indonesia - Wibowo, Andre Tri (Law Research Review Quarterly, 2021)
The phenomenon of 'Saracen' is one of the more serious cases in the context of cybercrime. It is not just a matter of fake news and hoax news, but 'Saracen' being an organized organization creates division, unrest, and slander in society, especially in general elections to influence society at large. This study aims to analyse the legal instruments in handling the 'Saracen Syndicate' case in Indonesia. This study finds that there are gaps in the rule of law in various cases of cybercrime, including the 'Saracen' case. On the one hand, this study confirms that there are elements of dirty political practices carried out during the general election, and on the other hand, this community develops because of the response from people who are thirsty for information (but are not careful in filtering the available information).